(untitled) (Medico Legal Update, 2021)
The COVID-19 is a globally problem influences in all function of life, from health to economic and political of countries. It is still to elevated in incidence and killed people specially among health workers. The study aimed to assess the psychological problems among health workers who work in health facilities at Babylon Province. Descriptive-analytic study conducted during the era of COVI-19 by using online GHQ-12 items as instrument to measure the symptoms of psychological problems. Convenience sample included 220 health workers participated in the study. The study revealed elevated in psychological problems among health workers and found significant relationship between gender and psychological problems. The study concluded to the support and available the enough training and medical health equipment may be reduced it.